Natural Convection Flow Of An Electrically Conducting Fluid In A Rectangular Cavity Having Internal Energy Sources With Linearly Heated Bottom Wall - Obayedullah, M; Chowdhury, M M K (GANIT: Journal of Bangladesh Mathematical Society, 2013)
Natural convection flow in a rectangular cavity containing internally heated and electrically conducting fluid has been investigated numerically. The bottom wall of the cavity is linearly heated whereas the top wall is well insulated. The left and right vertical walls are maintained at constant hot and cold temperature respectively.Results have been obtained with respect to Rayleigh numbers and Hartmann numbers. Flow and temperature fields for these cases have been studied. Average Nusselt numbers at hot, cold and linearly heated bottom wall have been calculated. It is found that the temperature, fluid flow and heat transfer strongly depend on internal and external Rayleigh numbers and Hartmann numbers. DOI: http://dx.doi.org/10.3329/ganit.v32i0.13648 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 32 (2012) 61-73